Point & Counterpoint Is CC BY the Best Open Access License? - Deborah Barreau (Journal of Librarianship and Scholarly Communication, 2012)
The only aim of scholarly communication should be the widest possible distribution of knowledge and scholarly results. In order for this to be possible, published research—which scholars give away for free to publishers—should be open access. And in this context, “gratis” open access (free to access) isn’t enough; only “libre” open access, which removes permission barriers, allows the widest distribution of knowledge.